2013
DOI: 10.1111/ejn.12097
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in the neural signature for the processing of behaviorally categorized and uncategorized speech sounds

Abstract: Recent human behavioral studies have shown semantic and/or lexical processing for stimuli presented below the auditory perception threshold. Here, we investigated electroencephalographic responses to words, pseudo-words and complex sounds, in conditions where phonological and lexical categorizations were behaviorally successful (categorized stimuli) or unsuccessful (uncategorized stimuli). Data showed a greater decrease in low-beta power at left-hemisphere temporal electrodes for categorized non-lexical sounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
(70 reference statements)
0
4
0
Order By: Relevance
“…Thus, the N400 effect should be observed in both interlocutor contexts (reflecting lexical integration), but a larger N400 effect is expected when participants process items uttered by monolingual (reflecting more efficient word/pseudoword discrimination). The N1 ERP response codes stimulus-specific features likely to be critical for speech perception 10 , and lexicality effects were also previously reported in such early time-windows when lexical access is facilitated and takes place very early in time after stimulus display 11 12 . If participants can predict a given language when facing a monolingual – but not a bilingual interlocutor –, we hypothesize that lexical access should be facilitated and speeded up.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Thus, the N400 effect should be observed in both interlocutor contexts (reflecting lexical integration), but a larger N400 effect is expected when participants process items uttered by monolingual (reflecting more efficient word/pseudoword discrimination). The N1 ERP response codes stimulus-specific features likely to be critical for speech perception 10 , and lexicality effects were also previously reported in such early time-windows when lexical access is facilitated and takes place very early in time after stimulus display 11 12 . If participants can predict a given language when facing a monolingual – but not a bilingual interlocutor –, we hypothesize that lexical access should be facilitated and speeded up.…”
mentioning
confidence: 54%
“…The ERP lexicality effect emerged earlier (N1 time-window) and was larger (N400 time-window) in the monolingual compared to the bilingual context. In fact, the N1 component was significantly larger for pseudo-words than for words 11 12 18 19 20 only in the monolingual interlocutor context. Later, in the [500–700] ms time-window, pseudo-words elicited a larger N400 component than words 6 7 8 9 in both interlocutor contexts.…”
Section: Discussionmentioning
confidence: 87%
“…The neural mechanism diverges between them: while the postdiction process is proposed to relate to theta-activity, the prediction process is proposed to relate to alpha-activity ( Gray et al, 2022 ). Typically, the postdiction process becomes more explicit and slower the neural process (i.e., probably related to enhanced theta activity), whereas the prediction processes are more implicit and probably related to faster neural activity, such as decreased alpha activity ( Gray et al, 2022 ) or beta activity ( Signoret et al, 2013 ). Although predictions are often primed implicitly in everyday conversation in their effect on RAMBPHO, contextual cues can be explicitly held in WM prior to the experimental materials ( Zekveld et al, 2013 ), in a similar vein to when postdiction feeds back into RAMBPHO.…”
Section: The Elu Model Takes Shapementioning
confidence: 99%
“…These results suggest that phonological and semantic knowledge improve the auditory detection of sounds. In a second study investigating the neural correlates of speech perception using electroencephalographic recordings (Signoret et al, 2013 ), participants were asked to categorize different types of sounds. The results showed that the amplitude of the N1 component elicited in the sensory cortex was smaller in response to words than in response to pseudo-words, and also smaller in response of pseudo-words than in response to complex sounds.…”
Section: On the Influence Of Knowledgementioning
confidence: 99%